DIGITAL COMMUNICATION STRATEGY OF THE @TEATERKELILINGIND INSTAGRAM ACCOUNT IN PROMOTING IMMORTAL THE MUSICAL: SI PITUNG - Cahya Wulandari Purnomo; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the digital communication strategy implemented by the @teaterkelilingind Instagram account in promoting the production of Immortal The Musical: Si Pitung. The research focuses on how Teater Keliling packages traditional cultural content to make it relevant and appealing to the younger generation through social media. A descriptive qualitative approach underpinned by the Computer Mediated Communication (CMC) theory was utilized in this study. Data collection was conducted through content observation, documentation, and in depth interviews with the production manager, head of social media, and a key informant from the audience. The results indicate that @teaterkelilingind successfully builds audience engagement by implementing a